(3cTa GdahGFO ef cJGH JegjO GdbhGYOs - (3GdYGedj, GHf GdMGLI, Rjf GdOjf Hf Ydj Hf CMeO, J (B966(3g`s ((3eMeO TajY Hf YHO GdhGMO ajQhRBHGOjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CeG HYO adeG cGf cTa GdahGFO ef cJGH JegjO GdbhGYO GdPj CdaJg (B...s
(3BNQgG (B:s
(3EPG Qhi GdUMGHj MOjKG Ke dbi GdfHj Udi Gddg Ydjg hSde gd jdReg SDGdg Ce dG(B... (3JMbjb eYfi bhdg JYGdi(B: (3djS ceKdg TjA, heYfi bhdg (B... (3Je agQSJ cJGH JegjO GdbhGYOs
(3JHUQI GdeDda (B:s
(3GdTgjO GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3(3, U(B64s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B741s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis